2016
DOI: 10.1103/physreva.94.040101
|View full text |Cite
|
Sign up to set email alerts
|

PT-symmetric slowing down of decoherence

Abstract: We investigate PT -symmetric quantum systems ultra-weakly coupled to an environment. We find that such open systems evolve under PT -symmetric, purely dephasing and unital dynamics. The dynamical map describing the evolution is then determined explicitly using a quantum canonical transformation. Furthermore, we provide an explanation of why PT -symmetric dephasing type interactions lead to critical slowing down of decoherence. This effect is further exemplified with an experimentally relevant systema PT -symme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 82 publications
1
30
0
Order By: Relevance
“…In the preceding subsections we presented the case for the Bures angle, which is the generalised geometric angle between density operators. However, for many applications one is not necessarily interested in how exactly the quantum states evolve, but one rather needs a quick estimate of, for instance, the typical flow of entropy [177] or the rate of decoherence [178]. Thus, a plethora of other speed limits have been discussed in the literature.…”
Section: Quantum Speed Limits For Other Quantitiesmentioning
confidence: 99%
“…In the preceding subsections we presented the case for the Bures angle, which is the generalised geometric angle between density operators. However, for many applications one is not necessarily interested in how exactly the quantum states evolve, but one rather needs a quick estimate of, for instance, the typical flow of entropy [177] or the rate of decoherence [178]. Thus, a plethora of other speed limits have been discussed in the literature.…”
Section: Quantum Speed Limits For Other Quantitiesmentioning
confidence: 99%
“…Among the nontrivial phenomena observed in these experiments are unidirectional invisibility in fiber networks [8], nonreciprocal light transport in whispering gallery microresonators [7], single-mode lasing in otherwise multimoded lasers with PT -symmetry [23,24], loss-induced lasing [6], control of emission direction of lasing in microring lasers [9], a mobility edge in disordered optical waveguide arrays [25,26], as well as chiral dynamics [16] and topological energy transfer when encircling an EP [19]. Recent years have also seen a number of very interesting theoretical proposals revealing how PT -symmetry can be used to enhance and control optomechanical interactions, and how PT -symmetry affects quantum phase transitions and information retrieval in quantum systems [27][28][29]. For example, the works of Jing et al with optomechanical microresonators have revealed the possibility of thresholdless phonon lasing [30], group veloc-1L 2L 1R 2R FIG.…”
Section: Introductionmentioning
confidence: 99%
“…This is because that experimental quantum systems are governed by Hermitian Hamiltonians. A possible approach is to realize a PT symmetric Hamiltonian in an open quantum system, but it is generally difficult to realize a controllable PT symmetric Hamiltonian by controlling the environment [22]. Some progress has been made with this approach in the system of light-matter quasiparticles [23,24].…”
mentioning
confidence: 99%